Tinjauan Kelengkapan Resume Medis Pasien Rawat Inap di Rumah Sakit Islam Jakarta Sukapura - Sansy Dua Lestari; Daniel Happy Putra; Deasy Rosmala Dewi; Laela Indawati (Yayasan Literasi Sains Indonesia, 2022)
Medical discharge is a summary of every action and treatment provided to the patient during hospitalization and must be signed by the DPJP doctor. The purpose of this study was to identify SOPs, determine the percentage of completeness of medical discharge and identify the factors causing the incompleteness. In this study, the method used is quantitative analysis method and data collection techniques are carried out through observation, quantitative analysis and interview guidelines, using the formula for estimating the proportion of the population of hospitalized patients in June and samples taken as many as 62 medical records. Based on the results of research and discussion, the completeness of the medical discharge at the Islamic Hospital of Jakarta Sukapura, the average percentage of completeness of the four components is 85.57% and the average incompleteness is 14.43%. Judging from the 4 components of quantitative analysis, the highest component of completeness analysis was found in the patient identification component 91.94% and the lowest was in the important note component 73.45%. Factors causing the incomplete filling of medical discharges are the absence of policies that regulate filling out medical discharges, the tight schedule of doctor's practice, and the lack of socialization of discipline in filling out medical discharges.